Prevalence and profile of users and non-users of anabolic steroids among resistance training practitioners - Ericson PEREIRA; Samuel Jorge MOYSES; Sérgio Aparecido IGNÁCIO; Daniel Komarchewski MENDES; Diego Sgarbi D. A. SILVA; Everdan CARNEIRO; Ana Maria Trindade Grégio HARDY; Edvaldo Antônio Ribeiro ROSA; Patrícia Vida Cassi BETTEGA; Aline Cristina Batista Rodrigues JOHANN (BMC, 2019)
Abstract Background To verify the prevalence and profile of users and non-users of anabolic steroid (AS) among resistance training practitioners. Methods An observational, cross-sectional survey was performed in 100 gyms in Curitiba city, involving 5773 individuals and self-administered questionnaires. The chi-square and z-tests of proportions were used for comparison between the groups (p < 0.05). Results 83.2% did not use, 9.1% formerly used, 3.4% currently used, and 4.3% intended used AS. The prevalence of former or current AS users was 16.9 and 6.5% among men and women, respectively. The prevalence ratios were as follows: 1) 2.6 male users for each woman; 2) 3.3 individuals aged 30-44 years and 2.8 individuals aged 18-29 years for each individual aged over 45 years. Beginners were not interested in using AS, but individuals who had trained longer had higher prevalence of AS use. Conclusions The gym environment encouraged the use of AS owing to aesthetic appeal. Thus, suggesting the need for actions to prevent abusive use of AS considering the practitioners profile (practitioners were young, university and single).